Security, Trust, and Transaction Convenience in Mobile Banking: A Moderated Mediation Model of Usage Decision and Satisfaction - Any Urwatul Wusko (Yayasan Ghalih Pelopor Pendidikan, 2026)
This study examines the structural relationships among security, trust, transaction convenience, usage decision, digital literacy, and user satisfaction in mobile banking. Drawing on Technology Acceptance Theory, trust theory in electronic commerce, and Expectation Confirmation Theory, the study develops a moderated mediation model to explain how and under what conditions mobile banking satisfaction is formed. Data were collected from 278 active users of Livin’ by Mandiri in Indonesia and analyzed using Structural Equation Modeling with Partial Least Squares. The results indicate that security strongly influences trust and directly enhances satisfaction, while transaction convenience and trust significantly affect usage decision. Usage decision is the strongest predictor of satisfaction and mediates the effects of trust and transaction convenience. Digital literacy strengthens the relationship between transaction convenience and usage decision, highlighting user capability as an important boundary condition. The findings provide theoretical advancement and practical insights for improving digital banking strategies in emerging markets.